Infectious Activity of L. Pasteur Rabies Virus Vaccine Strain Frozen-Dried in Various Protective Media And Then Stored at Various Temperatures - Varianytsia, Viktoriia V.; Vysekantsev, Igor P. (Problems of Cryobiology and Cryomedicine, 2019)
In this research, we studied the survival of industrial L. Pasteur rabies virus vaccine strain after freeze-drying in various protective media and further storage at 5, –20 and –80°C. After 24-month storage (the observation period), the highest rates of the virus infectious activity were found after storage at –80°C in all the media. The maximum virus survival was found in the DMEM-based protective medium, supplemented with 0.5% bovine serum albumin, 1% gelatin and 5% sucrose. The infectious activity of the specimens, frozen-dried in the media, containing either 5% sucrose or 3% gelatin and 5% sucrose, or 10% sucrose was significantly lower. The supplement of 3% gelatin to a protective medium was established to significantly increase the time of preparations dissolution as compared to other media and the regulation standard (i. e., not more than 1 min), that could complicate their practical use. The time of specimens’ dissolution with 1% gelatin and 5% sucrose or 10% sucrose was significantly longer if comaring to those with 5% sucrose, but complied with the production regulations Probl Cryobiol Cryomed 2018; 28(4): 333-342